Implementation of an On-the-Job Training Method in a Distance Education Environment - Balat, Şener; Karaman, Selçuk (International Review of Research in Open and Distributed Learning, 2025)
The aim of this study was to implement on-the-job training (OJT) in a distance learning environment. To achieve this, job analyses were conducted on spring semester beekeeping activities at a vocational school in the eastern Anatolia region of Türkiye, and content and activities were designed with an OJT environment prepared. Participants received a task video and checklist to be completed weekly during the relevant week of the season. They were required to record and send videos while performing tasks, with feedback provided, and they were encouraged to participate in expert/peer communication activities. Initially, participants completed tasks correctly at an 80% rate, which increased to 85% after feedback. Task completion levels were examined, showing higher levels for short, simple, and less risky tasks. The application showed a positive effect on academic achievement in favor of the final test.